The resolution of professional tennis disputes - Ilias Bantekas (7628027) (2023)
The regulatory landscape of professional tennis is scattered across several entities, each administering its own tournaments. This article focuses on disputes involving professional tennis players. In this context, it identifies two major areas of disputes, namely regulatory (encompassing disciplinary, doping and corruption offences) and contractual. The latter are chiefly resolved through litigation. Regulatory disputes are administered through distinct judicial and quasi-judicial institutions set up by the various tennis entities. The International Tennis Federation’s (ITF) international adjudication panel and its independent tribunal are the key institutions in this respect, with the independent tribunal possessing all the attributes of arbitral tribunals. The Court of Arbitration for Sport (CAS) has been conferred a limited appellate jurisdiction over decisions of these two entities. Overall, the ITF’s dispute resolution architecture has been effective and has created a significant body of precedent, further supplemented by that of the CAS. Other Information Published in: Journal of International Dispute Settlement License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/jnlids/idad010